2008
DOI: 10.1080/13547500701775563
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and biological variation of biomarkers of oxidative stress during the menstrual cycle

Abstract: Little information is available on the intra-individual variability of oxidative stress biomarkers in healthy individuals and even less in the context of the menstrual cycle. The objective of this study was to characterize the analytical and biological variability of a panel of 21 markers of oxidative damage, antioxidant defence and micronutrients in nine healthy, regularly menstruating women aged 18-44 years. Analyses included measurement of lipid peroxidation, antioxidant enzymes and antioxidant vitamins. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 71 publications
(54 reference statements)
5
36
0
Order By: Relevance
“…Covas et al [23] reported that II for SOD and glutathione peroxidase in human blood was 0.45 (low individuality), suggesting that it has little value as a diagnostic or screening tool. The components of variation for MDA in human plasma reported in the literature [18,24] are similar to our values. The RCV is an important clinical tool for the assessment of changes in patient animal being monitored in pathologicalsituations [24,25] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Covas et al [23] reported that II for SOD and glutathione peroxidase in human blood was 0.45 (low individuality), suggesting that it has little value as a diagnostic or screening tool. The components of variation for MDA in human plasma reported in the literature [18,24] are similar to our values. The RCV is an important clinical tool for the assessment of changes in patient animal being monitored in pathologicalsituations [24,25] .…”
Section: Discussionsupporting
confidence: 80%
“…Limited studies have been conducted to address these methodological issues [17,18] and there is still controversy over which oxidative stress biomarkers and LDH to use. It has been suggested that oxidative stress biomarkers and LDH should be utilized for research purposes until more sensitive and specific assays are developed [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…The variability in responses may, e.g., derive from non-standardized time difference between astaxanthin intake and blood sampling, a fl uctuating background intake from the diet, variable bioavailability, large distribution volume, (induced) degradation and others. High intra-and inter-individual bioavailability of carotenoids has been previously reported [15][16][17] and the present data on astaxanthin appear as no exception to this rule.…”
Section: Discussionmentioning
confidence: 44%
“…The mechanisms that relate ROS with female fertility are not completely understood. Investigation of the relationships between ROS and female fertility and reproductive outcomes may be masked by normal menstrual cycle variation [4] . In order to comprehensively evaluate the relation between ROS and infertility, physiological variations across the normal estrous cycle in healthy cows should be known.…”
Section: Introductionmentioning
confidence: 99%